DRAWING ASSEMBLY DRAWINGS USING AUTOCAD COMPUTER GRAPHICS SOFTWARE - Ismail Odilboyevich Ozodboyev (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the development of spatial thinking and imagination of pupils and students, the formation of concepts, skills and experiences in drawing and processing assembly drawings of great economic importance in production using the AutoCAD computer graphics program. raised